The Interference of the Indonesian Language in Arabic Communication at Modern Islamic Boarding School - Saepurrohman, Aep; Solihat, Zahra Anwariyatus; Karim, Agus; Bahaaeldin, Mohamed Saad (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
The gap in research on Arabic language interference in Indonesian Islamic boarding schools (pesantren) lies in the predominant focus on formal classroom contexts, while understanding of its manifestation in daily informal communication remains limited. This study addresses this gap by investigating interference from Indonesian into Arabic during non-classroom interactions among female students (santri putri) of the Modern Robithoh Islamic Boarding School in Bandung. Using an intrinsic qualitative case study approach, data were collected through observation, interviews, and documentation, and analyzed interactively. The findings reveal phonological, morphological, syntactic, and semantic interference, influenced by first language dominance, limited Arabic proficiency, psychological factors, and the sociolinguistic environment. These interference patterns negatively affect fluency and accuracy in Arabic. In response, the boarding school implements language development and immersion programs. This study highlights its novelty by exploring interference in the informal domain and recommends broader comparative studies and the integration of digital media to enhance communicative competence.